STANDARDIZATION OF KI-67 AS A BIOMARKER OF CELL PROLIFERATION - Zhylkibayev, A.A.; Sarina, N.I.; Mun, E.A.; Eskendirova, S.Z. (Eurasian Journal of Applied Biotechnology, 2019)
Currently, the most informative, accessible, and common method for evaluating the level of cell proliferative activity is identification and quantification of Ki-67 protein as a universal proliferation biomarker. The Ki-67 antigen is a component of the nuclear matrix, and nuclear core localization changes are observed during the cell cycle. Ki-67 protein is mainly associated with the chromosomes and belongs to the family of perichromonucleic proteins that surround chromosomes during mitosis. Ki-67 is characterized as a large nuclear protein based on cloning and sequencing a cDNA library. It is subjected to conformational changes during the cell cycle. Ki-67 also undergoes post-translational modifications by phosphorylation, accompanied by redistribution from the nucleoplasm into the perichromosomal layer and back during mitosis. Accordingly, Ki-67 is a widely used biomarker for cancer cells, including for pathological diagnosis and monitoring treatment responses. In particular, determination of the expression level of Ki-67 plays an important role in distinguishing the molecular subtypes of breast cancer and is one of the main criteria for determining the appropriate scheme of chemotherapy. However, there is currently no standardization of evaluation methods for predicting the disease outcome and effectiveness of chemotherapy. Researchers have reported the high variability in the Ki-67 index between different laboratories, depending on the choice of primary antibodies, methods for conducting immunohistochemistry, and methods for quantifying expression. The most appropriate threshold values of Ki-67 expression for clinical monitoring are continuously debated, and determination of a single cut-off point of Ki-67 was shown to not appropriately reflect the heterogeneous biology of the disease. In accordance with the latest recommendations of the St. Gallen conference of 2015, low, medium, and high Ki-67 thresholds were identified to achieve a better response to therapy. Here, we discuss the structure and function of the protein, as well as progress toward achieving a standardized determination method of Ki-67.